Can Descriptive Representation Help the Right Win Votes from the Poor? Evidence from Brazil - Frey, Anderson; Desai, Zuheir (John Wiley and Sons Inc, 2023)
The electoral success of the Right in poor nations is typically attributed to nonpolicy appeals such as clientelism. Candidate profiles are usually ignored because if voters value class-based descriptive representation,it should be the Left that uses it. In this article,we develop and test a novel theory of policy choice and candidate selection that defies this conventional wisdom: it is the Right that capitalizes on descriptive representation in high-poverty areas. The Right is only competitive in poor regions when it matches the Left's pro-poor policies. To credibly shift its position,it nominates candidates who are descriptively closer to the poor. Using a regression discontinuity design in Brazilian municipal elections,we show that Right-wing mayors spend less on the poor than Left-wing mayors only in low-poverty municipalities. In high-poverty municipalities,not only does the Right match the Left's policies,it also does so while nominating less educated candidates. © 2021 The Authors. American Journal of Political Science published by Wiley Periodicals LLC on behalf of Midwest Political Science Association.
Keywords: ODS 1 - Fin de la pobreza; ODS 10 - Reducción de las desigualdades; ODS 16 - Paz, justicia e instituciones sólidas